Economic culture building technology for academic physical education system - Bryzgalov, I.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to provide a theoretical basis for the new economic training technology for the national physical education universities. The economic training methods may be listed as follows. Traditional methods, with their natural limitations as they provide mostly for the one-way education flow (from teacher to student) with the student considered an object for requirements and tests; with his/ her progress rated and encouraged, regress penalized; and motivations secured by the public opinion, persuasion, practicing, teaching, stimulation, tests and progress rates. These methods need to be complemented by many reasonably managed techniques including success situations, hyperboles, highlights, pauses, focuses, contrasts, subtexts, hints, compromises, agreements, guidelines, etc. Results and conclusion. The proposed economic training technology complementary to the traditional academic physical education curricula is designed customizable to the latter and manageable, since the universities have all necessary test tools to verify its practical benefits. It is also important that the economic training technology and discipline is reproducible and user-friendly in application, i.e. may be implemented at every university provided the curriculum, educational service guidelines and textbooks are available.